Mawqif al-Syeikh Muhammad Taqi al-Uthmani fi Masalah al-Ta'widh 'An Dharar al-Matal fi Bai' al-Taqsit - Abd.Rahman, Noor Naemah (Jurnal Fiqh, 2010)
All human being should practice transparency in their behavior, in this matter, it is possible to use the values of Islam and It?s believes as an important instrument. The objective of this research is to clarify the rule of compensation for the harms caused by the procrastination (in payment of debt) in the light of the Shariah to Muhammad Taqi 'Uthmani; and also applied comparative method. By comparing his view with the views of 'Abd Allah bin Sulayman al-Muni? and Mustafa al-Zarqa, which showed that compensation for the harms caused by the procrastination is not permitted. This opinion is superior as described by Muhammad Taqi 'Uthmani because the verses of the Quran which 'Abd Allah bin Sulayman al-Muni? and Mustafa al-Zarqa had provided as an evidence are outside the field of compensation for the harms caused by procrastination of payment. Similarly, the prophetic tradition which they provided as evidence cannot be applied in compensating the harms caused by procrastination of payment by financial penalty. But it can be referred to a temporary solution to stop procrastination to oblige the debtor to donate as much as is known.